The Roles of Glial Cell Line-Derived Neurotrophic Factor, Tumor Necrosis Factor-α, and an Inducer of These Factors in Drug Dependence - Minae Niwa; Atsumi Nitta; Kiyofumi Yamada; Toshitaka Nabeshima (Elsevier, 2007)
There are few efficacious medications for drug dependence at present. Recent evidence has suggested that various cytokines are involved in the effects of abused drugs, suggesting that these factors play a role in drug dependence. In this article, the roles of glial cell line-derived neurotrophic factor (GDNF) and tumor necrosis factor-α (TNF-α) in drug dependence are discussed. GDNF inhibits the cocaine-induced upregulation of tyrosine hydroxylase activity in the ventral tegmental area and blocks behavioral responses to cocaine. TNF-α attenuates rewarding effects and locomotor sensitization induced by methamphetamine (METH) and morphine (MOR). Moreover, we mentioned the potential of Leu-Ile, which induces the expression of GDNF and TNF-α, as a novel therapeutic agent for drug dependence. Leu-Ile inhibits not only the development but also the maintenance of METH- or MOR-induced place preference and locomotor sensitization in mice. The inhibitory effect of Leu-Ile on METH- or MOR-induced place preference is not observed in GDNF heterozygous and TNF-α knockout mice. Leu-Ile inhibits METH- or MOR-induced place preference and sensitization by attenuating the METH- or MOR-induced increase in extracellular dopamine levels in the nucleus accumbens via the induction of GDNF and TNF-α expression. These findings suggest that Leu-Ile could be a novel therapeutic agent for drug dependence. Keywords:: glial cell line-derived neurotrophic factor, tumor necrosis factor-α, methamphetamine, morphine, Leu-Ile